ABOUT FACTORS INFLUENCING ON ELIMINATION OF HYDROGEN IN CIRCULATING VACUUMATOR OF RUP “BMZ” FOR KILLED AND UNKILLED STEELS - A. A. Chichko; V. F. Sobolev; D. M. Kukuj; N. V. Andrianov; V. V. Pivtsaev (Литьë и металлургия, 2006)
The characteristics of the vacuum degassing process in RH-vacuumator of RUP are experimentally investigated. The profiles of vacuumator pressure, discharge of argon, metal temperatures and others for different melting processes of cord steel assortment are determined.